COMPARISON OF INTRAVENOUS LABETALOL AND ORAL NIFEDIPINE IN MANAGEMENT OF BLOOD PRESSURE IN PATIENTS WITH SEVERE PREGNANCY INDUCED HYPERTENSION - Tehseen Aslam; Nuzhat Parveen; Shakeela Irfan; Uzma Riaz; Amin Anjum (Journal of University Medical & Dental College, 2019)
ABSTRACT: It is estimated that 6-12% of all the pregnancies are complicated by hypertension and even all improvements pre eclempsia is a signiﬁcant reason of maternal and perinatal morbidity and mortality worldwide. Nifedipine, Labetalol and hydralazine are mostly being used in acute management of hypertension in pregnancy but so far there is no evidence that anyone drug is more eﬀective. OBJECTIVE: To compare the mean time to achieve blood pressure control of oral Nifedipine with intravenous Labetalol for management of severe pregnancy induced hypertension. METHODOLOGY: This randomized control trial was done in Obstetrics and Gynaecology department of Hilal-e-Ahmer hospital, Faisalabad over a period of 6 months from 01-07-2016 to 31-12-2016. Total 100 patients (group-A and group–B having 50 in each) were included in study. In group A, females were given 40mg oral Nifedipine and in group, females were given 20ml intravenous Labetalol. Time at administration was followed in the ward for assessment of blood pressure control. Blood pressure was noted after every 10 min. The total donation time to achieve B.P was noted (as per operational deﬁnition).The collected data was analyzed by using SPSS version 17.0. Baseline blood pressure were presented in the form of mean+SD. Both groups were compared for mean time to achieve blood pressure control by applying t- test and consider signiﬁcant at p value <5%. RESULTS: Patients were ranged between 20-40 years. Mean age of the patients was calculated as 26.98+4.54 and 27.36+4.43 years in group-A and B respectively. Gestational age shows that 64%(n=32) in Group-A 74%(37%) in Group–B were between 20-30 weeks of gestation while 36%(n=18) in Group-A were between 31-40 weeks of gestation mean±SD was calculated as 28.92+4.91 and 28.94+4.72 weeks in Group-A and B respectively. Mean time to achieve B.P control in group A was 31.24+5.62 and in group B 45.5+4.63 with p value <0.05. CONCLUSION: Mean time to achieve blood pressure control was shorter with oral Nifedipine when compared to I/V Labetalol for management of female presenting with severe pregnancy induced hypertension.